A Schistosoma haematobium-specific real-time PCR for diagnosis of urogenital schistosomiasis in serum samples of international travelers and migrants. - Lieselotte Cnops; Patrick Soentjens; Jan Clerinx; Marjan Van Esbroeck (Public Library of Science (PLoS), 2013)
BACKGROUND: Diagnosis of urogenital schistosomiasis by microscopy and serological tests may be elusive in travelers due to low egg load and the absence of seroconversion upon arrival. There is need for a more sensitive diagnostic test. Therefore, we developed a real-time PCR targeting the Schistosoma haematobium-specific Dra1 sequence. METHODOLOGY/PRINCIPAL FINDINGS: The PCR was evaluated on urine (n = 111), stool (n = 84) and serum samples (n = 135), and one biopsy from travelers and migrants with confirmed or suspected schistosomiasis. PCR revealed a positive result in 7/7 urine samples, 11/11 stool samples and 1/1 biopsy containing S. haematobium eggs as demonstrated by microscopy and in 22/23 serum samples from patients with a parasitological confirmed S. haematobium infection. S. haematobium DNA was additionally detected by PCR in 7 urine, 3 stool and 5 serum samples of patients suspected of having schistosomiasis without egg excretion in urine and feces. None of these suspected patients demonstrated other parasitic infections except one with Blastocystis hominis and Entamoeba cyst in a fecal sample. The PCR was negative in all stool samples containing S. mansoni eggs (n = 21) and in all serum samples of patients with a microscopically confirmed S. mansoni (n = 22), Ascaris lumbricoides (n = 1), Ancylostomidae (n = 1), Strongyloides stercoralis (n = 1) or Trichuris trichuria infection (n = 1). The PCR demonstrated a high specificity, reproducibility and analytical sensitivity (0.5 eggs per gram of feces). CONCLUSION/SIGNIFICANCE: The real-time PCR targeting the Dra1 sequence for S. haematobium-specific detection in urine, feces, and particularly serum, is a promising tool to confirm the diagnosis, also during the acute phase of urogenital schistosomiasis.